2016
DOI: 10.1007/s00440-016-0693-5
|View full text |Cite
|
Sign up to set email alerts
|

Random matrices: tail bounds for gaps between eigenvalues

Abstract: Gaps (or spacings) between consecutive eigenvalues are a central topic in random matrix theory. The goal of this paper is to study the tail distribution of these gaps in various random matrix models. We give the first repulsion bound for random matrices with discrete entries and the first super-polynomial bound on the probability that a random graph has simple spectrum, along with several applications. Mathematics Subject Classification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 41 publications
(106 reference statements)
4
76
0
Order By: Relevance
“…Upper bounds on the probability of two close eigenvalues were proved by Nguyen, Tao and Vu [22]. Recently, universality of local eigenvalue statistics for deformed Wigner ensembles was studied by O'Rourke and Vu [23], Knowles and Yin [15, Section 12] and Lee, Schnelli, Stetler, and Yau [16].…”
Section: (Mean Density Of States) For Any Intervalmentioning
confidence: 99%
“…Upper bounds on the probability of two close eigenvalues were proved by Nguyen, Tao and Vu [22]. Recently, universality of local eigenvalue statistics for deformed Wigner ensembles was studied by O'Rourke and Vu [23], Knowles and Yin [15, Section 12] and Lee, Schnelli, Stetler, and Yau [16].…”
Section: (Mean Density Of States) For Any Intervalmentioning
confidence: 99%
“…We remark that a form of level repulsion was obtained in [24,27] for Wigner ensembles under no smoothness assumptions on the matrix elements. However, the estimates obtained are not strong enough for our methods.…”
Section: Proof Of Theorem 42mentioning
confidence: 99%
“…Weaker level repulsion estimates but with no smoothness condition were obtained in [24,27]. The proof of [11] was modified in [6] to include the case when the Wigner ensemble is not smooth but instead is the sum of a (possibly non-smooth) Wigner matrix and an independent Gaussian part.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we will exploit advances in Littlewood-Offord theory recently developed by Rudelson and Vershynin [24,26,31]. The authors' previous work [20] also used a stochastic approach to study controllability properties of random systems and was based on recent advances by Tao and Vu [28] and Nguyen, Tao, and Vu [18] concerning gaps between eigenvalues of random matrices. There it is shown that the controllability and minimal controllability of systems is a generic property, even for systems of a very discrete nature.…”
Section: 1mentioning
confidence: 99%